Smoking is Associated with Increased Blood Loss and Transfusion Use After Lumbar Spinal Surgery. Issue 4 (April 2016) - McCunniff, Peter T.; Young, Ernest S.; Ahmadinia, Kasra; Ahn, Uri M.; Ahn, Nicholas U.
Abstract: Background: Little is known about the association between smoking and intraoperative blood loss and perioperative transfusion use in patients undergoing spinal surgery. However, we found that although many of the common complications and deleterious effects of smoking on surgical patients had been well documented, the aspect of blood loss seemingly had been overlooked despite data reported in nonorthopaedic sources to suggest a possible connection. Questions/Purposes: We asked: (1) Is smoking associated with increased estimated blood loss during surgery in patients undergoing lumbar spine surgery? (2) Is smoking associated with increased perioperative transfusion usage? Methods: Between 2005 and 2009, 581 lumbar decompression procedures (with or without fusion) were performed at one academic spine center. Of those, 559 (96%) had sufficient chart documentation to categorize patients by smoking status, necessary intra‐ and postoperative data to allow analysis with respect to bleeding and transfusion‐related endpoints, and who did not meet exclusion criteria. Exclusion criteria included: patients whose smoking status did not fit in our two categories, patients with underlying coagulopathy, patients receiving anticoagulants (including aspirin and platelet inhibitors), history of hepatic disease, history of platelet disorder or other blood dyscrasias, and patient or family history of any other known bleeding disorder. Smoking history in packs per day was obtained for all subjects. We defined someone as a smoker if the patient reported smoking up until the day of their surgical procedure; nonsmokers were patients who quit smoking at least 6 weeks before surgery or had no history of smoking. We used a binomial grouping for whether patients did or did not receive a transfusion perioperatively. Age, sex, number of levels of discectomies, number of levels decompressed, number of levels fused, and use of instrumentation were recorded. The same approaches were used for transfusions in all patients regardless of smoking history; decisions were made in consultation between the surgeon and the anesthesia team. Absolute indications for transfusion postoperatively were: a hemoglobin less than 7 g/dL, continued symptoms of dizziness, tachycardia, decreased exertional tolerance, or hypotension that failed to respond to fluid resuscitation. Multiple linear regression analyses correcting for the above variables were performed to determine associations with intraoperative blood loss, while logistic regression was used to analyze perioperative transfusion use. Results: After controlling for potentially relevant confounding variables noted earlier, we found smokers had increased estimated blood loss compared with nonsmokers (mean, 328 mL more for each pack per day smoked; 95% CI, 249‐407 mL; p < 0.001). We also found that again correcting for confounders, smokers had increased perioperative transfusion use compared with nonsmokers (odds ratio, 13.8; 95% CI, 4.59‐42.52). Conclusions: Smoking is associated with increased estimated surgical blood loss and transfusion use in patients undergoing lumbar spine surgery. Patients who smoke should be counseled regarding these risks and on smoking cessation before undergoing lumbar surgery. Level of Evidence: Level III, therapeutic study.